Kontruksi Media Terhadap Pemberitaan Kasus Narkoba Medina Zein Dalam Pembentukan Opini Publik - Leliana, Intan (LPPM Universitas Bina Sarana Informatika, 2020)
People obtain knowledge or information about problems that occur in society through communication media, one of which is through mass media. The slightest problem can develop quickly because of the news through the mass media. The increasingly important role of the media in the formation of public opinion is inseparable from the rapid increase in information and communication technology. One of the news that had become viral in all mass media was the case of the arrest of a public figure Medina Zein about his involvement as a drug user. This study uses a qualitative approach that tries to collect as many drug cases as possible that have made his career ruined. This phenomenon shows that when someone who has a position is entangled with drugs, his career is threatened. Drug prevention and eradication measures are not only carried out by the National Narcotics Agency and the TNI. The reason is, these efforts must get support from a number of related elements. Currently the country is on the verge of collapse due to rampant drug trafficking. This is marked by the difficulty of declaring an area free from drug trafficking. Keyword: drugs, public opinion, Public Figure